A STUDY ON THE EFFECTS OF DEMONETIZATION AND COVID -19 ON KERALA RETAIL INDUSTRY - P. Pratheesh, K.Rajalakshmi (Journal of Informatics Education and Research, 2025)
The retail sector in Kerala experienced unprecedented challenges arising from the double crises of demonetization and COVID-19 . This review paper summarizes existing research literature to examine how these crises have affected the retail sectors of Kerala, highlighting production changes, consumer behavior, business convergence, and economic repercussions. Demonetization initially caused a massive cash shortage that severely disrupted small and medium retailers who were heavily reliant on cash transactions. However, it also catalyzed the change to digital payments, resulting in progressive financial inclusion. Comparatively, the restrictions imposed from the onset of the COVID-19 pandemic resulted in much longer closures of store fronts, a collapse of the supply chain, and a reduced propensity for consumers to spend, all of which plagued unorganized retailers more than others. Research indicates that while the impact of demonetization was acute but of a short-lived duration, COVID-19 was much longer in duration and cause a structural change in retail via an increase e-commerce and contactless transactions. Kerala further benefitted from its unique socio-economic characteristics, including high literacy, reliance on migrant labour, and strong cooperatives, which assisted in lessening the second shock. Furthermore, government directed initiatives such as monetary stimulus packages and capital investments in digital infrastructure assisted recovery, but provide less assistance to the micro-industry. This review outlined three important learning opportunities for understanding retail in Kerala Additionally, future research can focus on the post pandemic trust consumer have realised in digital systems, as well as discussing sustainable retail models for changing market conditions in Kerala. This paper has examined the dual crises, providing a full perspective on vigour and adaption in the retail sectors of Kerala, while also providing invaluable insights for their future policy making and business intent.